Economic theory and exhaustible resources - Dasgupta, Partha (Cambridge University Press, 1979)
A presentation of the economic principles relating to the use and management of natural resources, including analysis of optimal use policies
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Wirtschaft; Natural resources; Economics; Erschöpfbare Ressourcen; Rohstoff; Wirtschaftstheorie; Knappheit; Rohstoffwirtschaft